Analysis of call detail records to inform the COVID-19 response in Ghana—opportunities and challenges. (23rd June 2021) - Li, Tracey; Bowers, Rachel; Seidu, Omar; Akoto-Bamfo, Gloria; Bessah, David; Owusu, Victor; Smeets, Laurent
Abstract: Telecommunications data are being explored by many countries as a new source of data that can be incorporated into their national statistical systems. In particular, "mobile positioning data" are increasingly being used to study population movements and population distributions. However, the legal, ethical, and technical complexities of working with this type of data often pose many barriers, which can prevent the data from being used at the times when it is most urgently needed. We demonstrate how having a robust public–private partnership framework, a privacy-preserving technical setup, and a communications strategy already in place, prior to an emergency, can enable governments to harness the advantages of telecommunications data at the times when it is most valuable. However, even once these foundations are in place, the challenges of competing priorities, managing expectations, and maintaining communication with data consumers during a pandemic mean that the potential of the data is not automatically translated into direct impact. This highlights the importance of sensitisation exercises, targeted at potential data users, to make clear the potential and limitations of the data, as well as the importance of being able to maintain direct communication with data users. The views expressed in this work belong solely to the authors and should not be interpreted as the views of their institutions.